Normy etyczne obowiązujące pracodawców. Perspektywa systemu prawnego, organizacji i pracownika - Cieślikowska, Monika; Pieczewski, Andrzej (Annales. Etyka w Życiu Gospodarczym, 2013)
The aim of this article is to point out the basic areas of judgment made by employees considering the ethical or unethical behaviour of employers in the workplace. The authors analyse this subject from three perspectives: The first one is labour legislation in Poland; the second is the perspective of employers, especially codes of ethical standards created by contemporary organizations, and the third perspective is the point of view of employees. The conclusions in this area have been made on the basis of research in two Polish insurance companies. The authors attempted to create a ranking of ethical elements significant for employees. Such knowledge could be very useful for creating proper personnel policy in any organisation.